2022
DOI: 10.3389/fmolb.2022.974722
|View full text |Cite
|
Sign up to set email alerts
|

A cuproptosis-related lncRNA signature identified prognosis and tumour immune microenvironment in kidney renal clear cell carcinoma

Abstract: Kidney renal clear cell carcinoma (KIRC) is a heterogeneous malignant tumor with high incidence, metastasis, and mortality. The imbalance of copper homeostasis can produce cytotoxicity and cause cell damage. At the same time, copper can also induce tumor cell death and inhibit tumor transformation. The latest research found that this copper-induced cell death is different from the known cell death pathway, so it is defined as cuproptosis. We included 539 KIRC samples and 72 normal tissues from the Cancer Genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Earlier research has demonstrated that the acidic pH in the TME also impacts the efficacy of immunotherapeutic agents ( 7 ). In the present study, significant differences were excited in the expression of immune checkpoints between the two risk groups, which were linked to the immunosuppressive microenvironment ( 35 ). We also observed that the risk score was positively correlated with the TMB.…”
Section: Discussionmentioning
confidence: 63%
“…Earlier research has demonstrated that the acidic pH in the TME also impacts the efficacy of immunotherapeutic agents ( 7 ). In the present study, significant differences were excited in the expression of immune checkpoints between the two risk groups, which were linked to the immunosuppressive microenvironment ( 35 ). We also observed that the risk score was positively correlated with the TMB.…”
Section: Discussionmentioning
confidence: 63%
“…Dihydrolipoamide Branched Chain Transacylase E2 (DBT), a key enzyme in transforming α-keto acid into acyl-CoA, served as a protective factor in cervical cancer [ 53 ]. FOXD2-AS1 and LINC02154 are the risk factors for KIRC patients [ 48 , 54 , 55 ]. Furthermore, some epigenetics regulators can modulate cuproptosis, including m6A.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, researchers have identified and validated a lncRNA model of necroptosis that effectively predicts the survival of patients with glioma ( Wu et al, 2022 ). Numerous studies have been published highlighting the ability of cuproptosis-related lncRNAs (CRLs) to predict the survival of patients with breast cancer ( Jiang et al, 2022 ), hepatocellular carcinomas ( Zhu et al, 2022 ) and renal clear cell carcinomas ( Xin et al, 2022 ). However, to the best of our knowledge, there has been no systematic evaluation of whether CRLs can be utilized as biomarkers for the prognosis and treatment of glioma.…”
Section: Introductionmentioning
confidence: 99%